ESR1 Mutations in Breast Cancer: Proof of Concept Challenges Clinical Action - Gu, Guowei (Clin Cancer Res, 2015)
Wang and colleagues demonstrate that digital droplet PCR (ddPCR) identified ESR1 mutations in 7% of primary breast cancers. ESR1 mutations were also readily detected in metastatic tissues and circulating tumor DNA in the blood. These results suggest that ddPCR may be amendable for monitoring tumor burden, and to predict relapse.